KREATIVITAS KOMUNIKASI SALES DALAM MENJUAL PRODUK SMARTPHONE PASCA PANDEMI COVID-19 - Iis Mardiansyah; Trisnawati Kusumawardhani (Universitas Baturaja, 2023)
This study highlights the evolution of personal selling strategies at Company X, a retail smartphone business in Bekasi, amidst the COVID-19 pandemic and the New Normal. Employing a qualitative approach and case study methodology, the research explores how the integration of creativity in personal selling communication and the utilization of digital technologies, such as social media and communication applications, have become pivotal in product sales in the post-pandemic era. The study focuses on four primary sales strategy stages: planning, policy dissemination, implementation, and evaluation, along with an analysis of the distribution of sales personnel across different locations. The findings reveal that the creative use of social media, particularly Instagram, TikTok, Facebook, and WhatsApp, has successfully maintained consumer engagement and enhanced brand visibility in a competitive and digital environment. These insights underscore the importance of strategy adaptation, professionalism in digital content, and sales team training to meet the evolving market challenges. The study recommends improvements in sales team training, the optimization of social media use, and adaptability to market changes as key to future sales success.